Genetic parameters and diversity studies of yield and yield contributing characters in Brassica genotypes: Genetic parameters and divergence in Brassica (Journal of the Bangladesh Agricultural University, 2019)
The potential of a crop to favorably respond to breeding programs depends on its existing nature and magnitude of genetic variability, heritability and genetic advance. An experiment was conducted with eighteen Brassica genotypes following Randomized complete block design (RCBD) with three replications at the field of the department of Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh, Bangladesh to estimate genetic divergence, variability ranges and contribution of each trait towards genetic diversity. Analysis of variance showed significant variation among the genotypes for all the studied yield and yield contributing characters. The phenotypic co-efficient of variation (PCV) was higher than the genotypic co-efficient of variation (GCV) for all the characters measured, indicated that the traits were influenced by environment. All traits showed high heritability (61.54% to 98.64%) which indicated possible improvement through selection. High heritability values (>60%) along with high genetic advance and genetic advance in percentage of mean indicated prevalence of additive gene action, which provides good scope for further improvement by selection. The genotypes were grouped into four clusters, most of the genotypes were grouped into Custer I (8 genotypes), while cluster IV contained only one genotype. Considering the mean value, the cluster IV and Cluster II were ranked as the top groups in terms of yield and early maturity. High Heritability with high genetic advance in percentage of mean was observed for number of branches/plant, number of pod/plant, number of seeds/pod and yield/plant and selection focused   on these traits could be useful for future breeding program of Brassica. The genotype BD-7114 was the best performer considering all the studied traits especially yield and days to maturity which could be used as an important breeding material for the improvement of Brassica.J Bangladesh Agril Univ 17(3): 295–300, 2019